Uber and Traffic Fatalities - Anderson, Michael L.; Davis, Lucas W. (The Review of Economics and Statistics, 2026)
Abstract Previous studies of the effect of ridesharing on traffic fatalities have yielded inconsistent conclusions. We revisit this question using proprietary data from Uber measuring monthly rideshare activity at the Census tract level. We find a consistent negative effect of ridesharing on traffic fatalities, with impacts concentrated during nights and weekends. Our results imply that ridesharing has decreased U.S. traffic fatalities by 5.2% in areas where it operates. The annual life-saving benefits are $6.8 billion. Back-of-the-envelope calculations suggest that these benefits are of similar magnitude to producer surplus captured by Uber shareholders or consumer surplus captured by Uber riders.